Mountains under Pressure - Marchant, Rob; Cuni-Sanchez, Aida (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Mountain forests and alpine ecosystems are rich in biodiversity and endemism, and they are also large global carbon stores. They are highly threatened by climate change, population growth and land use change. Mountains represent an ideal natural laboratory in which the evolution of social-ecological systems can be investigated and to the current challenges and opportunities that this past evolution has created can be assessed. Mountains have been centres of past development and conduits for the spread of crops, populations and technologies. They were and remain a locus for cultural interaction, as manifested recently in many parts of the world at the local level through pastoral-agricultural-urban interactions over access to space and resources, particularly water. The relevance and impact of this Special Issue on mountains goes beyond academia, as practitioners and policymakers need key information on the dynamics and changes in threatened ecosystems to help design and implement appropriate management strategies for sustainable mountain futures.